First fossils records of chondrichthyes from Venado Formation, Upper Miocene, Alajuela Province, Costa Rica - Argüello-Sáenz, Alejandro (2022)
Remains of selachians have been collected at the Gabinarraca cave. These fossils were found in grainstone type lithoacies from the Upper Miocene carbonated lagoon and estuarine sediments of Venado Formation. Among the sharks remains are notorious the juvenile specimens of Carcharocles megalodon associated to a shallow marine and brackish waters environments. The discovery of these remains shows that species such as Carcharocles megalodon used the shallow waters of the Miocene where Venado de San Carlos is currently located as a breeding area.